PERAN ORANG TUA MEMBERIKAN PENDIDIKAN ISLAM TERHADAP ANAK MASA GOLDEN AGE DI LOK TUAN KOTA BONTANG - zainuddin zainuddin (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
This research aims to determine the real conditions of the Lok Tuan community, supporting and inhibiting factors, as well as alternative solutions used by parents in providing Islamic education to children during the golden age. This type of research is qualitative research and the location of this research is in Lok Tua Village, North Bontang District, Bontang City, using guidance and psychological approaches. The data in this research comes +-+from primary and secondary data, while data collection uses observation, interviews, and documentation methods. Next, the data obtained from the field will be processed and analyzed to conclude. The results of this research show that the role of parents in providing Islamic education to children during the golden age, especially in the Lok Tuan sub-district, still does not receive special attention due to the demands of work outside the home, so they choose to entrust their children to more familiar children's research centers. baby sitter